Aged care residents' prioritization of care: A mixed‐methods study. (21st January 2021) - Ludlow, Kristiana; Churruca, Kate; Mumford, Virginia; Ellis, Louise A.; Braithwaite, Jeffrey
Abstract: Background: Eliciting residents' priorities for their care is fundamental to delivering person‐centred care in residential aged care facilities (RACFs). Prioritization involves ordering different aspects of care in relation to one another by level of importance. By understanding residents' priorities, care can be tailored to residents' needs while considering practical limitations of RACFs. Objectives: To investigate aged care residents' prioritization of care. Design: A mixed‐methods study comprising Q methodology and qualitative methods. Setting and participants: Thirty‐eight residents living in one of five Australian RACFs. Method: Participants completed a card–sorting activity using Q methodology in which they ordered 34 aspects of care on a pre‐defined grid by level of importance. Data were analysed using inverted factor analysis to identify factors representing shared viewpoints. Participants also completed a think‐aloud task, demographic questionnaire, post‐sorting interview and semi‐structured interview. Inductive content analysis of qualitative data was conducted to interpret shared viewpoints and to identify influences on prioritization decision making. Results: Four viewpoints on care prioritization were identified through Q methodology: Maintaining a sense of spirituality and self in residential care; information sharing and family involvement; self‐reliance; and timely access to staff member support. Across the participant sample, residents prioritized being treated with respect, the management of medical conditions, and their independence. Inductive content analysis revealed four influences on prioritization decisions: level of dependency; dynamic needs; indifference; and availability of staff. Conclusions: Recommendations for providing care that align with residents' priorities include establishing open communication channels with residents, supporting residents' independence and enforcing safer staffing ratios.